Variants in LAMC3 Causes Occipital Cortical Malformation - Qian, Xiaohang; Liu, Xiaoying; Zhu, Zeyu; Wang, Shige; Song, Xiaoxuan; Chen, Guang; Wu, Jingying; Cao, Yuwen; Luan, Xinghua; Tang, Huidong; Cao, Li (Frontiers in Genetics, 2021)
Occipital cortical malformation (OCCM) is a disease caused by malformations of cortical development characterized by polymicrogyria and pachygyria of the occipital lobes and childhood-onset seizures. The recessive or complex heterozygous variants of the LAMC3 gene are identified as the cause of OCCM. In the present study, we identified novel complex heterozygous variants (c.470G>A and c.4030+1G>A) of the LAMC3 gene in a Chinese female with childhood-onset seizures. Cranial magnetic resonance imaging was normal. Functional experiments confirmed that both variant sites caused premature truncation of the laminin γ3 chain. Bioinformatics analysis predicted 10 genes interacted with LAMC3 with an interaction score of 0.4 (P value = 1.0e-16). The proteins encoded by these genes were mainly located in the basement membrane and extracellular matrix component. Furthermore, the biological processes and molecular functions from gene ontology analysis indicated that laminin γ3 chain and related proteins played an important role in structural support and cellular processes through protein-containing complex bindingand signaling receptor binding. KEGG pathway enrichment predicted that the LAMC3 gene variant was most likely to participate in the occurrence and development of OCCM through extracellular matrix receptor interaction and PI3K-Akt signaling pathway.